Justice, ethics and violence - Chamberlain, Francisco (2003)
I have been asked to work on the issue of ethics and violence. Both terms are highly complex. Let's start with a reflection on justice, because ethics is about what is fair in human life. If I am not mistaken, it was the Greek philosopher Aristotle who, 2,500 years ago, proposed the definition of justice that continues to guide reflection on this subject to this day. He said, in effect, that justice refers to the treatment we give and receive, that is, that justice is about what is owed to each one, what each one deserves.